Análisis del impacto de la implementación del beneficio tributario establecido en la Ley Orgánica de Discapacidades y su reglamento enfocado al impuesto fiscal a la propiedad vehicular periodos 2012-2014 - Rojano Oyola, Vanessa Guadalupe (2016)
In the different tax regimes worldwide there are certain benefits for taxpayers and the Ecuador part of these benefits are aimed at groups of taxpayers for a certain condition, are more vulnerable than others. That is why in this research work is to analyze the impact of a particular benefit to one group of citizens priority as indicated in the Constitution of the Republic. The vehicle ownership tax is a tax that must be paid to the State on an annual basis, together with the other components of the vehicle registration. This tax has an economic basis for calculating the same, the value corresponding to the commercial value of the vehicle and, according to current tax legislation, has a special rebate for qualified as disabled by the appropriate governmental entity people. This special discount according to the tax legislation is based on a fixed value decreased eight thousand dollars a valuation of the vehicle; however, this reduction is concerned with the provision of the Organic Law on Disabilities discriminating against the reduction according to the percentage of disability which has the owner of the vehicle, making progressive rebate whose highest degree or level of disability possess, get more tax benefit for this tax.